2017
DOI: 10.1016/j.jacc.2017.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Status of Early-Career Academic Cardiology

Abstract: Early career academic cardiologists, whom many believe are an important component of the future of cardiovascular care, face a myriad of challenges. The Early Career Section Academic Working Group of the American College of Cardiology (ACC) along with senior leadership support, assessed the progress of this cohort from 2013–2016 with a global perspective. Data consisted of accessing National Heart Lung and Blood Institute (NHLBI) public information, American Heart Association and international organizations pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…A majority of 70% of physician–scientist members of the American College of Cardiology (ACC) in their early careers devote less then 40% of their time to research. Overall, a quarter of early career academic cardiologists engage in basic and translational science [9]. Clinically, practicing general or interventional cardiology at an academic center are both possible.…”
Section: Career Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of 70% of physician–scientist members of the American College of Cardiology (ACC) in their early careers devote less then 40% of their time to research. Overall, a quarter of early career academic cardiologists engage in basic and translational science [9]. Clinically, practicing general or interventional cardiology at an academic center are both possible.…”
Section: Career Optionsmentioning
confidence: 99%
“…A higher percentage of effort for basic research means that physicians are more dependent on grants for salary support and have less clinical time, but on the other hand are eligible for more grants from NIH and AHA, and may be more competitive when applying for the same grants as scientists. However, the success rates of ACC members with substantial research commitment (40–75% of time) with regard to securing NIH grants declined by about 50% between 2013 and 2016 despite overall increased NHLBI funding [9]. Lack of time, lack of proper mentoring, and lower incomes than those of full-time clinicians are often criticized in this context.…”
Section: Career Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentorship is often perceived as critical for success in academic medicine as well as private practice. Cardiologists at all levels, especially during their early career, face challenges when it comes to advancing in research, teaching, and clinical practice development ( 1 , 2 ). A mentor is traditionally considered to be a senior colleague who has established knowledge or skill in a particular area and is willing to share that knowledge while helping to promote the career of a more junior physician.…”
mentioning
confidence: 99%
“…One of the major interventions that young investigators require assistance with is in securing grant funding where, of note, inadequate mentorship is cited as a major reason for rejection [5]. Unfortunately, the changing demographic of academia has led to a loss of effective mentors resulting in a significant decrease in external funding for young investigators that subsequently deters them from pursuing long-term academic careers [6]. Surprisingly, despite numerous publications on the critical importance of mentoring in academic medicine, few studies have demonstrated whether mentoring actually makes a difference and even fewer have been conducted on how to choose a suitable mentor [7–9].…”
mentioning
confidence: 99%